The utilisation of animation techniques in film: an analysis of Sin City as a form of film art - Shahkat Ali, Muhamad Sham (CGPublisher, 2009)
Animation is one of the six components in multimedia. Multimedia is infused with four components, graphics, audio, video and text. It is strengthened with the merging of computer generated imagery, animation and live-action filming. This merging creates a complete yet evolving entity of its own, creating for example commercials or feature length pictures. The ‘Sin City’ graphic novel and movie portray a harsh, grim and violent world in the lives and deaths of its characters because both represent or reflect real life immoral or injustice themes. For example, the unfairness of politics, the deceit of religious men, brutality to women, underworld societies, child abuse; that are happening in the world today. This particular graphic novel is adapted into a movie in the form of visual art. The aim of this research is to analyse the visual effects and identify the animation software used by the three animation houses (The Orphanage, CafeFX and Hybrid Technologies) in the production of “Sin City”. Content analysis is used to analyse the use of animation software and the visual effects produced for the movie version of this Frank Miller graphic novel. The units of analysis are (a) the main theme of ‘Sin City’ the movie, (b) the animation techniques in ‘Sin City’, (c) the visual effects for ‘Sin City’, the movie, including use of colour, and (d) the movie’s segments. The movie was chosen for its combination of art (graphic novel) and technology (animation techniques). This neo-noir movie made the impossible possible. “Impossible” here because the filmmaker and effects experts faced difficulties in their quest to bring ‘Sin City’ to the silverscreen. The study focuses on the production of a unique animated life-action movie using computer generated animation, showing that in producing a unique and realistic `world’, effective animation, in terms of 3D computer generated imagery techniques were used to generate the film noir look for the movie, similar to Miller’s graphic novels.